On Wrestling with Alienation and Producing More Progressive Mental Conceptions that Remake our World: Doing Democracy - Renner, Adam; McCrary, Nancye; Selwyn, Doug (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
Given rapidly increasing economic, environmental, political, and socio-cultural changes in what might be called a New Global Era, we examine the possibilities and challenges of democracy-in-action through education. We focus on empowering students to embrace justice and realize democracy-in-action by discussing civic-minded pedagogies and modeling student-centered techniques. Our primary aim is to engender discourse on teaching and learning social justice through student-centered pedagogical approaches that employ dialogic interaction and experiential learning to stimulate critical reflection and empower students.